Immunohistochemical Detection of Coxiella burnetii in Cattle Spleen Organs from Ampel Slaughterhouse, Boyolali Regency - Nugroho, Eko Prasetyo; Setiyono, Agus; Hadi, Upik Kesumawati; Winarsih, Wiwin; Astuti, Dwi (Jurnal Medik Veteriner, 2021)
Q-fever is a zoonotic bacterial disease that caused by Coxiella burnetii. These microorganism are gram negative and obligate intracellular bacteria. This study was conducted to detect C. burnetii in cattle organs which collected from Ampel slaughterhouse Boyolali Regency. In this study, spleen, heart, lung, liver and kidney were collected from 100 cattle. The samples were tested by immunohistochemical (IHC) method using polyclonal anti- C. burnetii antibodies. Immunohistochemical examination found the presence of C. burnetii in the cytoplasm of macrophage cells with specific brown color only in the spleen as many as 4 out of 100 cattle showing immunoreactive (4%). The four positive individual samples were from Simental cattle. These results indicate that Q-fever was found in local cattle in Boyolali Regency.